Preparation And Properties Of High Density Polyethylene (HDPE)/Soya Powder/Kenaf Core Biocomposites - Abdullah, Abdul Hamid (2011)
Mechanical, thermal, water absorption properties and morphologies of HDPE/soya powder/kenaf core biocomposites modified with maleic anhydride polyethylene (MAPE), γ-aminopropyltrimethoxysilane (γ-APS), acetic anhydride and oxidized polyethylene (OxPE) were investigated. The effect of filler loading was also studied. HDPE/soya powder/kenaf core biocomposites were prepared by incorporation of kenaf core powder at different filler loading (0, 10, 20, 30 and 40 phr) into HDPE/soya powder biocomposites with an internal mixer (Haake PolyLab) for 12 min at 180ºC and 50 rpm rotor speed. Results showed that the use of compatibilisers, silane coupling agent, and chemical modification by acetic anhydride on kenaf core filler has effectively introduce better matrix-filler interface interaction and consequently improved the mechanical properties of HDPE/soya powder/kenaf core biocomposites.